Modelling and forecasting WIG20 daily returns - Amado, Cristina (2017)
The purpose of this paper is to model daily returns of the WIG20 index. The idea is to consider a model that explicitly takes changes in the amplitude of the clusters of volatility into account. This variation is modelled by a positive-valued deterministic component. A novelty in speci cation of the model is that the deterministic component is speci ed before estimating the multiplicative conditional variance component. The resulting model is subjected to misspeci cation tests and its forecasting performance is compared with that of commonly applied models of conditional heteroskedasticity.